Racial Disparities in Clinical Outcomes of Takotsubo Cardiomyopathy: An Analysis of the National Inpatient Sample 2006 to 2018 - Chi N. Duong; Quoc V. P. Bui; Thomas Duong; Dai Q. Phan; Jan Mazur; Eugene Chung; Vien T. Truong (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background This study aimed to evaluate the impact of race on in‐hospital outcomes of Takotsubo cardiomyopathy using the National Inpatient Sample. Methods and Results We conducted a retrospective study using data from the National Inpatient Sample database 2006 to 2018. We focused on Takotsubo cardiomyopathy hospitalizations, excluding those with acute coronary syndrome as the primary diagnosis. Two study groups consisted of White patients or Black patients. Univariate and multivariable logistic models evaluated race's effect on death, cardiac arrest, cardiogenic shock, length of stay, while adjusting for potential confounders. The Bayesian model averaging technique was used to further elucidate the factors influencing death within each racial group. Significant differences were observed between the 2 racial groups. Black patients presented at a younger age, had a higher proportion of men, a higher burden of comorbidities, and a lower median household income compared with their White counterparts. In the univariate model, the Black cohort showed an increased risk of cardiac arrest (odds ratio, 1.45 [95% CI, 1.15–1.82]). However, the difference did not reach statistical significance in the multivariable model. Black patients also had a significantly longer hospital stay in both the univariate model (risk ratio, 1.26 [95% CI, 1.22–1.31]) and the multivariable model (risk ratio, 1.06 [95% CI, 1.04–1.07]). No significant difference in all‐cause death was observed between the racial groups. Conclusions The outcome differences between 2 racial groups in our study are likely influenced by racial disparities in demographics, comorbidities, and socioeconomic factors. Individualized care based on racial group needs is crucial in clinical practice.